THE EFFECT OF ASSOCIATED MEDIATION, LOYALTY, BRAND IMAGE AND THE QUALITY ACCEPTED TO THE EQUITY OF THE BRAND - Sarwani, Sarwani; Suprihhadi, Heru; Herawati, Andry (Economic and Bussiness Faculty, Dr Soetomo University, 2021)
One of the essential topics in marketing management is subject to brand equity. Initially, brand equity was recognized to can be given to bring added value to a product in the means corporate brand name. It is imperative to acknowledge that brand equity is an inseparable part of marketing and essential to the organization to create and build intense brand name organization experiences that will influence the decision-making process to brand name organization choice for membership. Thus, this study aims to prove and analyze the indirect influence amongst the brand equity dimensions on brand equity. For this study's purpose, brand equity dimensions include brand awareness, brand association, brand loyalty, brand image and perceived quality. In this study, a sum of 120 usable questionnaires from cooperation enterprises active membership was gathered. The result indicates that only a mediating influence brand loyalty of brand association on brand equity, and a mediating influence the perceived quality of the brand image on brand equity.